Cues, quantification, and agreement in language comprehension - Tanner, Darren; Bulkes, Nyssa Z. (Psychonomic Bulletin & Review, 2015)
We investigated factors that affect the comprehension of subject–verb agreement in English, using quantification as a window into the relationship between morphosyntactic processes in language production and comprehension. Event-related brain potentials (ERPs) were recorded while participants read sentences with grammatical and ungrammatical verbs, in which the plurality of the subject noun phrase was either doubly marked (via overt plural quantification and morphological marking on the noun) or singly marked (via only plural morphology on the noun). Both acceptability judgments and the ERP data showed heightened sensitivity to agreement violations when quantification provided an additional cue to the grammatical number of the subject noun phrase, over and above plural morphology. This is consistent with models of grammatical comprehension that emphasize feature prediction in tandem with cue-based memory retrieval. Our results additionally contrast with those of prior studies that showed no effects of plural quantification on agreement in language production. These findings therefore highlight some nontrivial divergences in the cues and mechanisms supporting morphosyntactic processing in language production and comprehension.